2020
DOI: 10.1021/acs.jpcc.0c08263
|View full text |Cite
|
Sign up to set email alerts
|

The Bright Side and Dark Side of Hybrid Organic–Inorganic Perovskites

Abstract: The previously developed bistable amphoteric native defect (BAND) model is used for a comprehensive explanation of the unique photophysical properties and for understanding the remarkable performance of perovskites as photovoltaic materials. It is shown that the amphoteric defects in donor (acceptor) configuration capture a fraction of photoexcited electrons (holes) dividing them into two groups: higher energy bright and lower energy dark electrons (holes). The spatial separation of the dark electrons and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…This is consistent with the fast diffusion of iodine atoms observed in MAPbI 3 and with the light induced halide interstitial mediated phase segregation in MAPb­(I 1– x Br x ) 3 alloys . It is also in general agreement with theoretical calculations that place the (0/−) charge transition state of I interstitial acceptor in the lower half of the band gap. , The identification of the localized deep defect as a halide interstitial suggests its close relationship with the BANDs which are two different configurations of iodine vacancy, as V I donor and a relaxed V MA + MA I acceptor configuration. , This connection has very important implications for understanding the photophysical properties and stability of HOIPs under illumination and will be discussed in a forthcoming work.…”
Section: Results and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is consistent with the fast diffusion of iodine atoms observed in MAPbI 3 and with the light induced halide interstitial mediated phase segregation in MAPb­(I 1– x Br x ) 3 alloys . It is also in general agreement with theoretical calculations that place the (0/−) charge transition state of I interstitial acceptor in the lower half of the band gap. , The identification of the localized deep defect as a halide interstitial suggests its close relationship with the BANDs which are two different configurations of iodine vacancy, as V I donor and a relaxed V MA + MA I acceptor configuration. , This connection has very important implications for understanding the photophysical properties and stability of HOIPs under illumination and will be discussed in a forthcoming work.…”
Section: Results and Discussionsupporting
confidence: 86%
“…More specifically, we demonstrated that bistable amphoteric native defects (BANDs) play an indispensable role in the formation of p−i−n junctions 6 and can account for the remarkable photophysical properties of HOIPs. 7 As has been shown previously 7 the BANDs represented by the anion dangling bond donor and halide dangling bond acceptor defects do not act as nonradiative recombination centers but rather reduce the recombination by partially separating photoexcited electrons from photoexcited holes.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Of course, one could expect such a shift in the case of very thin samples (as it can be related to quantum confinement and built-in strain), but here it was clearly observed in the whole investigated thickness range. Another possible explanation is related to the hypothesis that emission in HOIPs such as MAPbI 3 is governed by bistable amphoteric native defects (BANDs), i.e., defects whose nature (donor/acceptor) and formation energy are controlled by the location of Fermi energy. , Assuming that due to the increased surface-to-volume ratio in thinner films, the concentration of BANDs is higher, one can expect such a behavior of the PL peak. A further interesting feature in PL spectra is related to the thickness range between 50 and 225 nm.…”
Section: Resultsmentioning
confidence: 99%
“…defects whose nature (donor/acceptor) and formation energy are controlled by the location of Fermi energy. 42,43 Assuming that due to increased surface to volume ratio in thinner films the concentration of BANDs is higher one can expect such a behavior of PL peak. A further interesting feature in PL spectra is related to the thickness range between 50 nm and 225 nm.…”
Section: Thickness Of Mapbi3 Film (Nm) = 260ˑ[concentration Of Ink(m)...mentioning
confidence: 99%